Examining learning rates in the evaluation of academic interventions that target reading fluency. Issue 2 (27th December 2017) - Solomon, Benjamin G.; Poncy, Brian C.; Caravello, Devin J.; Schweiger, Emily M.
Abstract: The purpose of the current study is to determine whether single‐case intervention studies targeting reading fluency, ranked by traditional outcome metrics (i.e., effect sizes derived from phase differences), were discrepant with rankings based on instructional efficiency, including growth per session and minutes of instruction. Converging with prior findings, we found great variability in reported sessions and minutes of instruction across studies, as well as divergences in rankings based on outcome variables. These findings raise questions as to how literature syntheses on the topic of academic intervention are interpreted and how selection of evidence‐based intervention occurs.